(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
According to many researchers, the presence of pronunciation deficiencies is one of the reasons for the failure of elementary school children in the Russian language. As children do not know how to determine the number of sounds in a word, their sequence and they find it difficult to select words that begin with a given sound. Despite the good mental abilities of the child, due to the shortcomings of the sound side of speech, he/she cannot master the vocabulary and grammatical structure of speech in subsequent years. Children who do not know how to distinguish and isolate sounds by ear and pronounce them correctly find it difficult to master writing skills. This article presents an overview on formation of speaking skills of elementary school children in Russian lessons in order to reach the highest level of development of speech.